Body surface patch
The body surface adhesion material addresses the challenges of complex structures and poor tracking on uneven surfaces by using a simple structure with a radiation-curable resin and hydrophilic polymer compound adhesive layer, achieving enhanced handling, flexibility, and reduced adhesive flow.
Patent Information
- Application Number
- JP2018122743
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2018-06-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2038-06-28
AI Technical Summary
Existing body surface adhesion materials face challenges such as complex structures due to carrier sheets, poor tracking ability on uneven body surfaces, and increased risk of adhesive flow and residue when exposed to sweat and exudates.
A body surface adhesion material with a simple structure, comprising a substrate with a thickness of 20 to 90 μm, an adhesive layer made of a radiation-curable resin and a hydrophilic polymer compound, and a pressure-sensitive adhesive protective layer, which eliminates the need for a carrier sheet and enhances flexibility and elasticity.
The material achieves good handling during application, excellent tracking ability on uneven body surfaces, reduced adhesive flow, and effective absorption of sweat and exudates, leading to improved wound healing and reduced skin irritation.
Smart Images

Figure 0007649449000006 
Figure 0007649449000001 
Figure 0007649449000002
Abstract
Description
[Technical field]
[0001] The present technology relates to an adhesive material for a body surface, and more specifically, to an adhesive material for a body surface that can be attached to the skin or other body surfaces and used for protecting or treating the skin or wounds. [Background technology]
[0002] Various adhesive materials have been used for protecting and treating the skin and wounds, and for fixing medical materials and instruments such as gauze, bandages, and catheters to the surface of the body.
[0003] Generally, body surface patches are configured to be attached to the body surface by providing an adhesive layer on one side of a substrate. Such patches are required to be able to conform well to the unevenness and extension of the body surface, so thin, flexible sheet-like film materials are preferred as the substrate. However, when such film materials are used as the substrate, they are generally weak and easily bend or wrinkle when applied to the body surface, resulting in poor handling during application.
[0004] Therefore, a patch is known in which a carrier sheet that is stronger than the substrate is temporarily attached to the side of the substrate opposite the adhesive layer, and the carrier sheet is peeled off after the substrate is attached to the body surface (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-154872 Summary of the Invention [Problem to be solved by the invention]
[0006] However, providing a carrier sheet to the patch causes problems such as a complicated structure of the patch and a cumbersome application process. On the other hand, if the base material or adhesive layer is made thick or made of a material with stiffness in order to give the patch stiffness, problems arise such as poor conformability to the body surface after application or the patch becoming easily lifted and peeled off from the body surface.
[0007] Furthermore, if a large amount of plasticizer is added to the adhesive to impart flexibility and stretchability that enables it to follow the unevenness and extension of the body surface, the cohesive strength of the adhesive layer decreases, and if applied for a long period of time, the adhesive layer may protrude from the periphery and edges of the patch (hereinafter referred to as "flow"), causing problems such as the adhesion of dirt and the like and the residue of glue remaining when the patch is removed, resulting in a poor appearance of the body surface.
[0008] Therefore, the objective of the present technology is to provide a body surface patch that has a simple structure, is easy to handle when applied, has flexibility and stretchability that enables it to conform well to the irregularities and extension of the body surface after application, and can further reduce flow. [Means for solving the problem]
[0009] The present inventors have conducted intensive research in light of the above-mentioned circumstances and have found that the above-mentioned problems can be solved by setting the thicknesses of the substrate and the pressure-sensitive adhesive layer within specific ranges and further using a radiation-curable resin and a hydrophilic polymer compound in the pressure-sensitive adhesive layer, thereby completing the present technology.
[0010] That is, the present technology provides a body surface patch comprising a substrate having an upper surface and a bottom surface, an adhesive layer covering at least a portion of the bottom surface of the substrate, and a peelable adhesive protective layer covering the surface of the adhesive layer, wherein the substrate has a thickness of 20 to 90 μm, the adhesive layer has a thickness of 40 to 160 μm, and the adhesive layer contains at least a radiation curable resin and a hydrophilic polymer compound. Effect of the Invention
[0011] The body surface patch according to the present technology has a simple structure that does not have a carrier sheet, yet is easy to handle when applied, and has flexibility and stretchability that enables it to conform well to the irregularities and extension of the body surface after application, and can also reduce flow. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view of a body surface patch according to an example of an embodiment of the present technology. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, preferred embodiments for carrying out the present technology will be described with reference to the drawings. Note that the embodiments described below are representative embodiments of the present technology, and the scope of the present technology is not narrowly interpreted by them. In addition, the present technology can be combined with any of the following examples and their modifications.
[0014] 1, a body surface patch 1 according to the present technology comprises a base material 2 having an upper surface and a bottom surface, an adhesive layer 3 covering at least a portion of the bottom surface of the base material 2, and a peelable adhesive protective layer 4 covering the surface of the adhesive layer 3. Each part will be described in more detail below.
[0015] <About the substrate> As shown in FIG. 1, the base material 2 has an upper surface which is positioned on the outermost side when the body surface patch 1 according to the present technology is attached to the body surface, and a bottom surface on the opposite side.
[0016] The thickness of the substrate according to the present technology is preferably 20 to 90 μm, and more preferably 30 to 50 μm when used on a part that moves a lot, such as a fingertip. By setting the thickness of the substrate within the above range, the substrate can be easily handled when applied, and can exhibit flexibility and stretchability that can follow the unevenness and extension of the body surface after application.
[0017] The substrate of the present invention may be made of a film, foam, or fabric (nonwoven, woven, or knitted fabric). Of these, films are preferred in terms of flexibility, elasticity, appropriate water vapor permeability, bacterial barrier properties, and ease of wiping off dirt. Examples of the film material include polyurethane; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyamides such as nylon 6 and nylon 66; polyolefins such as polyethylene and polypropylene; olefin-based copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate copolymer (EMA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-methacrylic acid polymer (EMAA), and ethylene-acrylic acid copolymer (EAA); polyvinyl alcohol; polyvinyl chloride and polyvinylidene chloride; and silicones such as polydimethylsiloxane. Of these, polyethylene is preferred in terms of its appropriate stiffness and low cost of manufacture. These materials may be used alone or in combination of two or more.
[0018] The substrate according to the present technology can be made of a single material in a single form, or can be made of two or more materials in a composite form. Also, the substrate can be made of a laminated structure in which substrates of the same or different types are laminated.
[0019] <About the adhesive layer> As shown in FIG. 1, the pressure-sensitive adhesive layer 3 is provided so as to cover at least a portion of the bottom surface of the substrate 2.
[0020] The thickness of the adhesive layer according to the present technology is preferably 40 to 160 μm, and more preferably 80 to 100 μm when used on parts of the body that are subject to frequent movement, such as fingertips. By setting the thickness of the adhesive layer within the above range, the adhesive layer can be easily handled when applied, and can exhibit flexibility and stretchability that can follow the unevenness and extension of the body surface after application.
[0021] The pressure-sensitive adhesive layer according to the present technology is composed of a pressure-sensitive adhesive composition containing at least a radiation-curable resin and a hydrophilic polymer compound. The pressure-sensitive adhesive composition according to the present technology is a liquid having fluidity before being irradiated with radiation that causes curing of the radiation-curable resin contained in the pressure-sensitive adhesive composition. In this specification, the pressure-sensitive adhesive composition after being irradiated with radiation is referred to as a "pressure-sensitive adhesive" to distinguish it from the pressure-sensitive adhesive composition before being irradiated with radiation.
[0022] The form in which the radiation curable resin and the hydrophilic polymer compound are present in the pressure-sensitive adhesive composition according to the present technology is not particularly limited, but it is preferable that the radiation curable resin and the hydrophilic polymer compound are dispersed in a hydrocolloid form. The pressure-sensitive adhesive composition forms a hydrocolloid, which can absorb sweat and exudate from wounds and reduce rash and itching caused by sweating, and therefore the body surface patch according to the present technology can be suitably used as a wound dressing. Each component will be described in detail below.
[0023] (1) Radiation curable resins The "radiation curable resin" according to the present technology refers to a resin composition that is cured (or crosslinked) by irradiation with radiation and contains at least one of a polymer, an oligomer, and a monomer as a component. For example, the radiation curable resin may be a polymer of a monomer and a polymerization initiator, or an oligomer and a monomer that are cured (or crosslinked) by irradiation with radiation.
[0024] The "radiation" in the radiation curable resin is not particularly limited as long as it can impart energy to the pressure-sensitive adhesive composition to cause a curing (crosslinking) reaction by radical polymerization, cationic polymerization, anionic polymerization, etc. Examples of such radiation include electron beams, ultraviolet rays, infrared rays, laser beams, visible light, ionizing radiation (X-rays, α-rays, β-rays, γ-rays, etc.), microwaves, and high frequency waves.
[0025] The radiation curable resin according to the present technology is preferably one that undergoes a curing (crosslinking) reaction by one or more types of radiation selected from the group consisting of electron beams, visible light, and ultraviolet light. That is, the radiation curable resin is preferably one or more types selected from electron beam curable resins, visible light curable resins, and ultraviolet light curable resins. Of these, it is more preferable to use an ultraviolet light curable resin. In addition, the curing reaction mechanism of the radiation curable resin is not particularly limited, but is preferably a radical polymerization type, a cationic polymerization type, or a photodimerization reaction, and more preferably a radical polymerization type or a photodimerization reaction.
[0026] Examples of the resin type of the radiation curable resin include (meth)acrylate resin, silicone resin, urethane resin, silicone acrylate resin, urethane acrylate resin, and epoxy acrylate resin. These radiation curable resins may be used alone or in combination of two or more, or may be a mixture containing two or more. Of the above resin types, the radiation curable resin according to the present technology is preferably one or more selected from (meth)acrylate resin, silicone (meth)acrylate resin, urethane (meth)acrylate resin, and epoxy (meth)acrylate resin. In addition, it is more preferable to use an ultraviolet-curable (meth)acrylate resin as the radiation curable resin. In this specification, "(meth)acrylate" means both "acrylate" and "methacrylate".
[0027] As the radiation curable resin, it is preferable to use a polymer and / or copolymer having a structural unit (repeating unit) derived from a (meth)acrylate having an alkyl group having 1 to 20 carbon atoms, more preferably 2 to 10, and even more preferably 4 to 8 carbon atoms, or a cycloalkyl group having 4 to 8 carbon atoms. The alkyl group or cycloalkyl group may have a substituent, and examples of the substituent include a halogen atom, a hydroxyl group, an aryl group, an alkoxy group, a phenoxy group, an epoxy group, a norbornyl group, and an adamantyl group. As the radiation curable resin having such a structural unit, a polymer and / or copolymer having a structural unit derived from butyl (meth)acrylate and / or a structural unit derived from 2-ethylhexyl (meth)acrylate is more preferable, and a polymer and / or copolymer having a structural unit derived from butyl acrylate and / or a structural unit derived from 2-ethylhexyl acrylate is even more preferable. The polymer and / or copolymer having such a structural unit may be an oligomer having a lower molecular weight than the polymer, which will be described later.
[0028] Mass average molecular weight M of radiation curable resin w The M of the radiation curable resin is preferably 1,000 to 250,000, and more preferably 1,000 to 200,000. w By setting M within the above range, it is possible to obtain a pressure-sensitive adhesive composition having a low viscosity, and after irradiation with radiation, the mass-average molecular weight increases due to a curing reaction, making it possible to obtain a pressure-sensitive adhesive having a high cohesive strength. w is a value measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0029] Commercially available products can be used as the radiation curable resin according to the present technology. Examples of commercially available radiation curable resins include ThreeBond's "3000 Series" and "3100 Series", DIC's "Unidic" and "Tyforce" series, Mitsubishi Chemical's "Upima" series, Hitachi Chemical's "Hitaroid" series, Arakawa Chemical Industries, Ltd.'s "Beamset" series, BASF's "acResin" series, and Toagosei's "UVA-2000 Series".
[0030] The radiation curable resin may be constituted as a resin composition containing one or more polymerizable oligomers and / or monomers as components in addition to or instead of the polymers and / or copolymers having structural units derived from the above-mentioned (meth)acrylates. The polymerization form of the polymerizable oligomers and / or monomers is preferably radical polymerization or cationic polymerization, and more preferably radical polymerization.
[0031] Examples of oligomers capable of radical polymerization include (meth)acrylate oligomers, polyester acrylate oligomers, urethane (meth)acrylate oligomers, silicone (meth)acrylate oligomers, and epoxy (meth)acrylate oligomers.
[0032] Examples of monomers capable of radical polymerization include monomers having a (meth)acryloyl group. The number of (meth)acryloyl groups is not particularly limited, and examples include monofunctional (meth)acrylates having one (meth)acryloyl group, bifunctional (meth)acrylates having two (meth)acryloyl groups, and multifunctional (meth)acrylates having three or more (meth)acryloyl groups.
[0033] Examples of oligomers or monomers capable of cationic polymerization include oligomers or monomers having an epoxy ring, an oxetane ring, an oxolane ring, a dioxolane ring, and a vinyl ether structure, as well as oligomers or monomers having functional groups having these structures. Examples of cationic polymerizable oligomers or monomers include limonene oxide-based compounds available from Tomoe Engineering Co., Ltd., glycidyl ether-based compounds available from Kyoeisha Chemical Co., Ltd. under the trade name "Epolite" series, and oxetane-based compounds available from Toa Gosei Co., Ltd. under the trade name "Aron Oxetane". The radiation-curable resin according to the present technology preferably contains one or more polymerizable oligomers selected from (meth)acrylate-based oligomers, urethane (meth)acrylate-based oligomers, and silicone (meth)acrylate-based oligomers.
[0034] The molecular weight of the oligomer is not particularly limited, but for example, the number average molecular weight M n An oligomer having a number average molecular weight of less than 10,000 (for example, 1,000 or more and less than 10,000) can be used. An oligomer having a number average molecular weight of less than 10,000 is preferred because the viscosity of the adhesive composition does not become too high, and processing such as coating can be performed smoothly. n A polymerizable oligomer having a high molecular weight such as a polymer having a number average molecular weight M of 10,000 or more may be used. n is a value measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0035] The radiation curable resin may contain a polymerization initiator, an additive, a solvent, etc. The polymerization initiator is not particularly limited, and any polymerization initiator known in the field of radiation curable resins may be used, such as an acetophenone-based initiator, a benzophenone-based compound, an α-ketoester-based compound, and a benzoin-based compound.
[0036] The radiation curable resin preferably contains a polymerization initiator, but has the polymerization initiator bonded to the molecular chain of the polymer or oligomer of the radiation curable resin. By using a radiation curable resin having a polymerization initiator bonded to the molecular chain, it is not necessary to add a polymerization initiator, and a safer adhesive composition can be obtained. Examples of radiation curable resins having a polymerization initiator introduced into the molecular chain include the "UV-H" series manufactured by KSM Corporation and the "acResin" series manufactured by BASF. Note that a different polymerization initiator may be added to the radiation curable resin to which the polymerization initiator is already bonded, or may be replaced with another polymerization initiator.
[0037] Examples of oligomers or polymers capable of undergoing photodimerization include oligomers or polymers having a maleimide group. Examples of oligomers or polymers capable of undergoing photodimerization include terminal maleimide polyester resins or terminal maleimide polyether resins commercially available under the trade name "UVA-2000" series manufactured by Toagosei Co., Ltd.
[0038] The content of the radiation curable resin used in the present technology is not particularly limited, but is preferably 40 to 90 mass %, more preferably 50 to 80 mass %, of the total mass of the pressure-sensitive adhesive composition. By having the content of the radiation curable resin in the above range, the pressure-sensitive adhesive composition can be provided with good cohesiveness after being irradiated with radiation, and a hydrocolloid in which the hydrophilic polymer compound is dispersed in the radiation curable resin can be formed in a stable state.
[0039] (2) Hydrophilic polymer compounds The hydrophilic polymer compound according to the present technology is not particularly limited, and may be a natural, semi-synthetic or synthetic hydrophilic polymer compound. Note that "semi-synthetic" is also called partial chemical synthesis, and refers to chemical synthesis using a compound isolated from a natural resource such as a plant material, a microorganism or a cell culture as a starting material.
[0040] Specific examples of natural hydrophilic polymer compounds include plant-based polymers such as gum arabic, tragacanth gum, galactan, guar gum, carob gum, karaya gum, carrageenan, pectin, agar, and starch (e.g., rice, corn, potato, and wheat starch); microbial polymers such as xanthan gum, dextrin, dextran, succinoglucan, mannan, locust bean gum, and pullulan; and animal-based polymers such as casein, albumin, and gelatin.
[0041] Specific examples of semi-synthetic hydrophilic polymer compounds include starch-based polymers (e.g., carboxymethyl starch, methylhydroxypropyl starch, etc.); cellulose-based polymers (e.g., methyl cellulose, ethyl cellulose, methylhydroxypropyl cellulose, hydroxyethyl cellulose, sodium cellulose sulfate, hydroxypropyl cellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, etc.); alginic acid-based polymers (e.g., sodium alginate, calcium alginate, propylene glycol alginate, etc.); and the like.
[0042] Specific examples of synthetic hydrophilic polymer compounds include vinyl polymers (e.g., polyvinyl alcohol, polyvinyl methyl ether, polyvinylpyrrolidone, carboxyvinyl polymer, etc.); acrylic polymers (e.g., sodium polyacrylate, polyacrylamide, etc.); polyethyleneimine; and the like.
[0043] In the present technology, the hydrophilic polymer compound may be one of the above alone or two or more of them may be used in combination. Among these hydrophilic polymer compounds, it is preferable to use one or more selected from sodium carboxymethylcellulose, pectin, karaya gum, mannan, locust bean gum, and gelatin, and it is more preferable to use one or more selected from sodium carboxymethylcellulose, pectin, and gelatin. By including these hydrophilic polymer compounds in the adhesive composition, it is possible to easily form a so-called hydrocolloid. This allows the adhesive layer to absorb sweat and exudate from wounds, and reduces rash and itching caused by sweating.
[0044] The amount of the hydrophilic polymer compound used in the present technology is preferably 5 to 35% by mass, more preferably 10 to 30% by mass, based on the total mass of the pressure-sensitive adhesive composition. When the amount of the hydrophilic polymer compound is within the above range, moisture such as sweat and exudate can be absorbed well. In addition, skin irritation caused by skin maceration and the like is reduced, and the body surface patch according to the present technology can be applied for a long period of time.
[0045] (3) Other ingredients The adhesive composition according to the present technology may contain a tackifier, a filler, a pH adjuster, a medicinal ingredient, a softener (plasticizer), and the like, as necessary, within a range that does not impair the object of the present technology.
[0046] Furthermore, the pressure-sensitive adhesive composition according to the present technology may contain a non-functional acrylic polymer. By using a non-functional acrylic polymer, the viscosity of the pressure-sensitive adhesive composition can be effectively reduced, the flexibility of the pressure-sensitive adhesive can be increased, and the adhesive strength of the pressure-sensitive adhesive can be increased.
[0047] The "acrylic polymer" in the non-functional acrylic polymer is a polyacrylate or polymethacrylate, and refers to a polymer or copolymer having 50 mol% or more of structural units derived from acrylate and / or methacrylate as main structural units. This acrylic polymer preferably has 60 to 100 mol%, more preferably 70 to 100 mol%, and even more preferably 80 to 100 mol% of structural units derived from acrylate and / or methacrylate. The content (mol%) of structural units derived from acrylate and / or methacrylate in the acrylic polymer can be measured by NMR (nuclear magnetic resonance).
[0048] The term "non-functional" in the non-functional acrylic polymer means that the polymer does not substantially have any other functional groups besides acryloyl groups. In this case, examples of the other functional groups include OH, COOH, epoxy groups, and alkoxysilyl groups.
[0049] The mass average molecular weight (M w From the viewpoint of effectively reducing the viscosity of the pressure-sensitive adhesive composition and easily obtaining a pressure-sensitive adhesive having a high cohesive strength, M is preferably from 1,000 to 9,000, more preferably from 1,500 to 8,000, and even more preferably from 2,000 to 6,000. w is a value measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0050] In addition, from the viewpoint of effectively reducing the viscosity of the pressure-sensitive adhesive composition, the non-functional acrylic polymer according to the present technology is preferably liquid at room temperature (20 to 30° C.) The solid content of this non-functional acrylic polymer that is liquid at room temperature is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0051] The viscosity of the non-functional acrylic polymer at 25° C. is preferably 300 to 10,000 mPa·s, more preferably 400 to 6,000 mPa·s, and even more preferably 500 to 5,000 mPa·s. In this specification, the viscosity (steady flow viscosity) of the non-functional acrylic polymer at 25° C. is a value measured at 25° C. using a single cylindrical rotational viscometer in accordance with JIS Z8803.
[0052] From the viewpoint of effectively reducing the viscosity of the pressure-sensitive adhesive composition, the non-functional acrylic polymer has a glass transition point (T g ) is preferably −100 to −20° C., more preferably −90 to −40° C., and further preferably −80 to −60° C. g is a value measured by a differential scanning calorimeter (DSC).
[0053] In the present technology, the content of the non-functional acrylic polymer is not particularly limited, but is preferably 5 to 25 mass %, more preferably 10 to 20 mass %, of the total mass of the pressure-sensitive adhesive composition. By setting the content of the non-functional acrylic polymer within the above range, it becomes possible to effectively reduce the viscosity of the pressure-sensitive adhesive composition and effectively increase the cohesiveness of the pressure-sensitive adhesive.
[0054] The pressure-sensitive adhesive composition according to the present technology can have a dynamic viscosity at 115°C and 1 Hz, measured by the method in the Examples described below, of preferably 500 Pa s or less, more preferably 300 Pa s or less, and even more preferably 250 Pa s or less, before being irradiated with radiation. When the viscosity of the pressure-sensitive adhesive composition is within the above range, processing such as coating of the pressure-sensitive adhesive composition is easy to perform, and for example, coating with a hot melt processing device is also possible.
[0055] As described above in detail, in the pressure-sensitive adhesive composition according to the present technology, the radiation-curable resin is cured by irradiation with radiation, and therefore it is possible to obtain a pressure-sensitive adhesive with good cohesiveness after the radiation-curable resin is cured. From the viewpoint of obtaining a pressure-sensitive adhesive that is easy to apply and has good cohesiveness, it is preferable that the pressure-sensitive adhesive composition contains 40 to 90% by mass of the above-mentioned radiation-curable resin and 5 to 35% by mass of the above-mentioned hydrophilic polymer compound, and further contains 5 to 25% by mass of a non-functional acrylic polymer. A more suitable pressure-sensitive adhesive composition can be obtained by containing the preferred components detailed in this specification in a more preferred range. Specifically, it is preferable to form the adhesive layer from an adhesive composition containing 50 to 80 mass % of an ultraviolet-curable (meth)acrylate resin as the radiation-curable resin, 10 to 30 mass % of one or more hydrophilic polymer compounds selected from sodium carboxymethylcellulose, pectin and gelatin as the hydrophilic polymer compounds, and 10 to 20 mass % of a non-functional acrylic polymer that is liquid at room temperature (20 to 30°C) as the non-functional acrylic polymer.
[0056] (4) Manufacturing method of adhesive The pressure-sensitive adhesive according to the present technology is obtained by irradiating the pressure-sensitive adhesive composition with radiation, and is the pressure-sensitive adhesive composition after being irradiated with radiation. The adhesive according to the present technology may be a liquid having flowability, or may be a solid that retains the shape of, for example, a film or a sheet. In addition, both liquid and solid adhesives can be used as the adhesive layer according to the present technology.
[0057] In the irradiation step of irradiating the pressure-sensitive adhesive composition with radiation, the amount of radiation is not particularly limited as long as it is an amount of energy that can cause a curing reaction of the radiation-curable resin. For example, when a 100 μm-thick ultraviolet-curable resin is used as the radiation-curable resin, the cumulative amount of irradiation of ultraviolet light with a wavelength of 250 to 260 nm is 10 to 1000 mJ / cm. 2 It can be set appropriately within the range of 100 to 600 mJ / cm 2In addition, when an electron beam curable resin is used as the radiation curable resin, the cumulative dose of the electron beam can be appropriately set, for example, in the range of 1 to 100 kGy.
[0058] In the production of the adhesive according to the present technology, it is preferable to carry out a mixing step of mixing the adhesive composition before the irradiation step. The mixing method is not particularly limited, and for example, mixing can be carried out using a stirrer, a kneader, a roll, etc. The time, temperature, etc. in this mixing step are also not particularly limited, and are appropriately set depending on the components contained in the adhesive composition according to the present technology.
[0059] In addition, in producing the adhesive according to the present technology, it is preferable to carry out a step of filling a mold with the adhesive composition or dropping or applying it to a substrate (hereinafter, these steps are collectively referred to as a "coating step") before the above-mentioned irradiation step so that a uniform curing reaction occurs by radiation irradiation. The method for carrying out this coating step is not particularly limited, and a known method can be adopted. For example, a common method such as a comma coater, a die coater, a bar coater, a knife coater, a gravure roll, a reverse roll, a spin coat, a spray coat, a screen printing, a dipping, and a dispense can be used. Note that the adhesive according to the present technology is applied at a rate of 40 to 160 g / m2 relative to the substrate from the viewpoints of adhesive strength, skin conformability after application, and ease of handling during application. 2 It is preferably coated.
[0060] In addition, it is preferable to impart breathability during coating. Specifically, a method of applying tension to the adhesive composition by adjusting the gap between the die coater head and the back roll to randomly form vents can be mentioned. In addition, as another method, a method of pressing an embossing roll against the surface of the adhesive composition to transfer the unevenness of the embossing roll to the adhesive composition to form vents can also be mentioned. Furthermore, the adhesive composition may be transferred by passing the adhesive composition through the holes using a screen with holes formed at appropriate intervals in advance by screen printing, and providing a substrate on the back side.
[0061] Furthermore, the pressure-sensitive adhesive composition according to the present technology can be coated using a hot melt processing device. In this case, in consideration of the ease of coating and the heat resistance of the hydrophilic polymer compound in the pressure-sensitive adhesive composition, the coating temperature is preferably 60°C to 150°C, more preferably 70°C to 140°C, and even more preferably 80°C to 130°C.
[0062] <About the adhesive protective layer> 1, the adhesive protective layer 4 is provided removably and covers the surface of the adhesive layer 3. The adhesive protective layer 4 protects the adhesive layer 3 from contamination and the like, and makes the body surface patch 1 easier to handle.
[0063] The thickness of the adhesive protective layer according to the present technology is not particularly limited, but is usually preferably about 40 to 150 μm.
[0064] The adhesive protective layer according to the present technology can be made of any material used in conventional adhesive materials, such as synthetic resin film or paper. Examples of such materials include films of polyester, polyethylene, polypropylene, etc., films treated with a release agent such as silicone-based release agent, fluorine, or fluorine compounds, and paper. These protective films may also be embossed.
[0065] In addition, the adhesive protective layer according to the present technology may be made of a material with good UV transmittance so that it can be cured (or crosslinked) more quickly by UV irradiation. For example, a transparent film material such as polypropylene or polyethylene can be used. By using these, UV irradiation can be performed from both sides of the body surface patch, and curing (or crosslinking) can be performed quickly.
[0066] The adhesive protective layer according to the present technology may be one sheet as shown in Fig. 1. The adhesive protective layer may have one or more dividing sections at the center or end, or two or more adhesive protective layers may be provided with their side ends overlapping each other. With these configurations, even if one adhesive protective layer is peeled off, the other adhesive protective layer remains, and the adhesive layer can be applied to the body surface without touching the adhesive surface, improving workability.
[0067] <About body surface patches> The total thickness of the body surface patch according to the present technology (the sum of the thickness of the base material and the thickness of the adhesive layer) is preferably 60 to 250 μm, and more preferably 110 to 150 μm. If the total thickness of the body surface patch exceeds 300 μm, it may be difficult for the patch to conform to the unevenness or extension of the body surface after application, or the edges of the patch may easily get caught, causing the patch to peel off.
[0068] The shape of the body surface patch according to the present technology is not particularly limited, and can be, for example, a polygon such as a triangle, a square, or a diamond, a circle, an ellipse, or a sheet-like shape that is an appropriate combination of these shapes, a tape-like shape formed continuously in a specific direction, a roll-like shape, etc. In addition, it can be formed three-dimensionally according to the part to be applied, and it is also possible to provide cuts, slits, etc.
[0069] Examples of uses of the body surface patch according to the present technology include wound dressings applied to living bodies, surgical tapes, tapes for fixing catheters and infusion tubes, patches for ostomy appliances, compresses, patches for fixing electrocardiogram electrodes and magnetic therapy devices, and patches for skin care and beauty. In particular, as described above, the body surface patch according to the present technology uses an adhesive that forms a hydrocolloid, and is therefore suitable for use as a wound dressing. By using the body surface patch according to the present technology as a wound dressing, it is possible to effectively absorb moisture such as sweat and exudate from the wound, create a moist environment suitable for wound healing, and improve the wound healing effect.
[0070] The body surface patch related to this technology has a viscosity of 0.63 × 10 -7 It is preferable that the adhesive has a bending hardness (bending resistance) of mN·cm or more. By having a bending hardness (bending resistance) of the above value or more, it is possible to maintain an appropriate stiffness that makes it easy to apply. In this specification, the bending hardness (bending resistance) is measured by the method described in the examples below.
[0071] In addition, the load when stretched at 20% displacement of the body surface patch according to the present technology is preferably 6.0N / 20mm or less. By having a load when stretched of 6.0N / 20mm or less, it can follow the body surface well even if it moves, and can prevent discomfort during application. In particular, when used on a part that moves a lot, such as a fingertip, it is more preferable that the load when stretched is 4.0N / 20mm or less. In this specification, the load when stretched is measured by the method described in the Examples below.
[0072] The body surface patch according to the present technology preferably has a flow of -10 to +10% when dry and a flow of 10% or less after absorbing water. By having a flow within the above range, swelling of the hydrocolloid pressure sensitive adhesive at the end cross section during application can be prevented, and curling or peeling can be prevented. In this specification, the flow is measured by the method described in the Examples below.
[0073] Furthermore, the body surface patch according to the present technology preferably has a probe tack peak of 10 gf or more and a probe tack integral value of 20 to 50 gfs. By having a peak value of the above value or more, it is possible to prevent the patch from peeling off immediately after application. In addition, by having an integral value within the above range, the patch is easily adapted to the body surface after application and can exhibit appropriate adhesiveness. In this specification, the probe tack is measured by the method described in the Examples below.
[0074] The body surface patch according to the present technology preferably has a water absorption rate of 50% or more after 24 hours. By having a water absorption rate of the above value or more, it is possible to quickly absorb sweat, exudates, etc., and prevent deformation and adhesive residue when absorbing water or when peeling off. In addition, the body surface patch according to the present technology has a water absorption rate of 0.005 g / cm per unit area after 24 hours. 2 When the water absorption amount per unit area is equal to or greater than the above value, the adhesive is less likely to flow even after absorbing water, the shape of the adhesive material can be well maintained, and adhesive residue upon peeling can be prevented.
[0075] Furthermore, the body surface patch according to the present technology preferably has a visible light transmittance of 5.0% or more at a wavelength of 550 nm. By having a visible light transmittance of the above value or more, the appearance of the body surface patch when applied is improved, and the water absorption and the state of the body surface can be easily observed while the body surface patch is applied. This makes it possible to check the appropriate time to replace the applied body surface patch without peeling it off, and prevents water leakage and unnecessary replacement.
[0076] <Manufacturing method of body surface patch> The body surface patch according to the present technology can be manufactured by at least carrying out a coating step of dropping or applying the pressure-sensitive adhesive composition onto the surface of the substrate, and an irradiation step of irradiating the pressure-sensitive adhesive composition with radiation to cure it. Alternatively, the body surface patch according to the present technology can be manufactured by at least carrying out a coating step of dropping or applying the pressure-sensitive adhesive composition onto the surface of the pressure-sensitive adhesive protective layer, a step of attaching the substrate to the pressure-sensitive adhesive composition, and an irradiation step of irradiating the pressure-sensitive adhesive composition with radiation to cure it. Alternatively, the body surface patch according to the present technology can be manufactured by at least carrying out a coating step of dropping or applying the pressure-sensitive adhesive composition onto the surface of the pressure-sensitive adhesive protective layer, an irradiation step of irradiating the pressure-sensitive adhesive composition with radiation to cure it, and a step of attaching the substrate to the pressure-sensitive adhesive layer formed by curing it. The coating step and the irradiation step can be the same as those described in the above "Method of manufacturing pressure-sensitive adhesive". EXAMPLES
[0077] The present technology will be described in more detail below based on examples. Note that the examples described below are representative examples of the present technology, and the scope of the present technology is not to be interpreted narrowly by these examples.
[0078] Example 1 65.0% by mass of an ultraviolet-curable resin (BASF's product name "acResin A260UV", a polymer having a structural unit derived from butyl acrylate) as an example of a radiation-curable resin was heated to 120°C, and 20.0% by mass of sodium carboxymethylcellulose (hereinafter "CMC·Na", Nippon Paper Industries Co., Ltd.) as an example of a hydrophilic polymer compound and 15.0% of a non-functional acrylic polymer (ARUFON (registered trademark) UP-1000, Toagosei Co., Ltd.) were added and mixed and stirred. The mixture was then stored at a temperature where the viscosity became 150 Pa·s or less, to obtain a pressure-sensitive adhesive composition.
[0079] Next, the prepared pressure-sensitive adhesive composition was applied to paper that had been subjected to a release treatment using a silicone-based release agent using a die coater at 120°C to a thickness of 100 μm, and the integrated light amount at 250 nm to 260 nm (hereinafter referred to as "UVC irradiation amount") was 240 mJ / cm 2 Then, a PE film (thickness: 40 μm) as an example of a substrate was attached to obtain a body surface patch of Example 1.
[0080] (Examples 2 to 5) Except for changing the amount of adhesive applied and the amount of UVC irradiation as shown in Table 1, the same procedure as in Example 1 was carried out to obtain body surface patches of Examples 2 to 5.
[0081] Example 6 The adhesive composition was formulated to contain 80.0% by mass of ultraviolet-curable resin, 10.0% by mass of CMC·Na, and 10.0% by mass of non-functional acrylic polymer, and the thickness of the substrate was changed as shown in Table 1. In the same manner as in Example 1, the body surface patch of Example 6 was obtained.
[0082] Example 7 The composition was the same as in Example 6, and the body surface patch of Example 7 was obtained in the same manner as in Example 1, except that the type and thickness of the base material were changed as shown in Table 1.
[0083] (Reference examples 1 and 2) The composition was the same as in Example 6, and except that the type and thickness of the base material were changed as shown in Table 1, the same procedure was followed as in Example 1 to obtain body surface patches of Reference Examples 1 and 2.
[0084] <Experiment 1: Measurement of total thickness> For each of the body surface patches of the Examples and Reference Examples, the total thickness of the substrate and adhesive layer was measured using a dial thickness gauge (Peacock Model H) with a φ10 mm probe. The thickness of the adhesive layer was calculated by subtracting the thickness of the substrate from each total thickness.
[0085] <Experiment 2: Bending resistance test> The bending resistance of the body surface patch (hereinafter also referred to as "test piece") of each of the above-mentioned Examples and Reference Examples was measured using the "41.5° cantilever method" in accordance with JIS L 1912. Specifically, the test was carried out as follows. Two test pieces were prepared by cutting the body surface patch of each Example and Reference Example to a width of approximately 20 mm. The test piece was placed on a smooth horizontal platform with one end having a 41.5 degree slope, with the adhesive side facing up and the short side aligned with the front end of the platform. The test piece was then gently slid in the direction of the slope, and the protruding length of the test piece was measured when the center point of one end of the test piece came into contact with the slope of the horizontal platform. The protruding lengths of the two test pieces were measured, and the bending resistance (flexural hardness (mN·cm)) was calculated using the following formula (1). The bending length in formula (1) is half the length (cm) of the protruding length of the test piece.
[0086]
number
[0087] <Experiment 3: Load test during extension> For the body surface patches of each of the above Examples and Reference Examples, the load (N) at 20% displacement of the body surface patch was measured using a tensile tester (Shimadzu Corporation product name "Autograph AGS-X") in accordance with JIS Z0237, with a gripping distance of 20 mm and a tensile speed of 300 mm / min. In this experiment, the focus was on the fingers, which are particularly active on the body surface and for which the followability and comfort of the patch are important, and since the skin elongation rate when the fingers are bent at about 45 degrees is about 20%, the load at 20% displacement was used as an index. The dimensions of the test piece were 20 mm wide and 100 mm long.
[0088] <Experiment 4: Flow test> For the body surface patches of Examples 1 to 5, a pressure plate with a diameter of 18 mm was placed on top, and 5 g (approximately 2 g / cm) was applied in the thickness direction. 2 ) was applied, and the thickness of the body surface patch after 72 hours was measured using a dial thickness gauge (peacock model H) with a φ10 mm probe in an atmosphere of 37°C and 90% humidity. Note that the measurement was performed within 10 seconds after the load was removed, during which no creep recovery occurs. For each Example and Reference Example, tests were performed in a dry state and after immersion in physiological saline (0.9% NaCl aqueous solution) for 3 hours (hereinafter referred to as "after water absorption"), and the change rate (%) of thickness of the test piece before and after the load was applied was calculated.
[0089] <Experiment 5: Probe tack test> For the body surface patches of Examples 1 to 5, a TACKINESS TESTER (manufactured by RHESCA) was used to measure the probe tack when a load of 10 g was applied for 2 seconds at 37°C with a probe diameter of 5 mm and a descending speed of 30 mm / min, and then the test piece was separated from the probe at an ascending speed of 30 mm / min.
[0090] <Experiment 6: Water absorption test> The body surface patches of Examples 1 to 5 were immersed in physiological saline (0.9% NaCl aqueous solution) so that the adhesive layer of the base material was on the physiological saline side, and then left to stand in a thermostatic chamber at 37°C and 90% humidity. After 24 hours, the weight of the test piece was measured, and the water absorption rate (%) and the amount of water absorption per unit area (g / cm) were calculated using the following formula. 2 ) was sought.
[0091]
number
[0092]
number
[0093] <Experiment 7: Visible light transmittance test> Using an ultraviolet-visible spectrophotometer (Shimadzu Corporation, UV-1650PC), the transmittance of the body surface patch of each Example and Reference Example at a wavelength of 550 nm was measured. Note that in this experiment, the transmittance at a wavelength of 550 nm was measured because the wavelength of light that is easily visible to the human eye is 550 nm.
[0094] <Experiment 8: Skin patch evaluation test> As a representative example, the body surface patch of Example 3 was applied to the nail area and the second joint of the fingers of six subjects, and the ease of application, discomfort immediately after application, adhesion immediately after application, and inconspicuousness immediately after application were each evaluated on a 10-point scale. The evaluation criteria for each item are as follows.
[0095] (1)Easy to apply The ease of handling when applying the body surface patch of Example 3 to a nail or finger joint was evaluated with the following scale: 10 points: the patch has firmness and is easy to apply; 0 points: the patch has no firmness and is difficult to apply.
[0096] (2) Discomfort immediately after application The discomfort felt immediately after application of the body surface patch of Example 3 to the nail or knuckle was rated as follows: 10 points: the patch moves satisfactorily with the movement of the skin, and there is no foreign body sensation, resistance, or tightness of the skin; 0 points: the patch does not move with the movement of the skin, and there is a foreign body sensation, resistance, or tightness of the skin.
[0097] (3) Stickiness immediately after application The body surface patch of Example 3 was applied to the nail or knuckle, and the adhesion immediately after application was evaluated on the following scale: 10 points: tightly adhered to the skin; 0 points: came off immediately after application.
[0098] (4) Inconspicuous immediately after application The body surface patch of Example 3 was applied to a nail or a knuckle, and the inconspicuousness of the patch was evaluated with a score of 10: inconspicuous and 0: noticeable.
[0099] For the body surface patches of Examples 1 to 7 and Reference Examples 1 and 2, the production conditions and the results of Experiments 1 to 7 are shown in Table 1. The results of Experiment 8 are shown in Table 2.
[0100] [Table 1]
[0101] [Table 2]
[0102] As shown in Tables 1 and 2, the body surface patches of Examples 1 to 7 had a base thickness of 20 to 90 μm and an adhesive layer thickness of 40 to 160 μm, and therefore showed favorable results in bending hardness (bending resistance) and elongation load tests. In particular, the body surface patch of Example 3 was evaluated by subjects as being easy to handle when applied, and caused little discomfort immediately after application, even when applied around the nails or to the knuckles. Furthermore, the body surface patches of Examples 1 to 5 had a flow when dry of -10 to +10%, and a flow after absorbing water of 10% or less, meaning that the flow of the adhesive could be reduced. Furthermore, the body surface patches of Examples 1 to 5 had a probe tack peak of 10 gf or more and a probe tack integral value of 20 to 50 gfs, showing appropriate adhesiveness. In particular, the body surface patch of Example 3 was found to have good adhesion immediately after application in the evaluation by subjects. The body surface patches of Examples 1 to 5 have a water absorption rate of 50% or more, and therefore can rapidly absorb sweat, exudates, etc., and are excellent in preventing deformation and adhesive residue when absorbing water or peeling off. In addition, the water absorption per unit area is 0.005 g / cm 2 From the above, it was found that the patch was less likely to flow even after absorbing water, was able to maintain its shape well, and was excellent in preventing adhesive residue when removed. Furthermore, since the body surface patches of Examples 1 to 7 have a visible light transmittance of 5.0% or more, it was found that water absorption and the condition of the body surface can be easily observed while the patch is still attached, and the appropriate time to replace the patch can be determined without removing it. Furthermore, the body surface patch of Example 3 was also found to be excellent in terms of inconspicuousness when applied, as evaluated by subjects.
[0103] As described above, the body surface patches of Examples 1 to 7 have good handleability due to moderate stiffness, show good conformity to the movement of the body surface, and do not cause irritation or discomfort. Among them, the body surface patches of Examples 1 to 5 show moderate bending hardness (bending resistance) and load at extension, and are considered to have excellent handleability when applied and conformity after application, especially when applied to areas with small circumferences and frequent movements such as around the nails and finger joints. In addition, the body surface patches of Examples 1 to 5 have good adhesion immediately after application and do not peel off during application. Furthermore, since the total thickness of the base material and the adhesive layer is thin, there is no catching of the edges when applied, and the adhesive flow is unlikely to occur.
[0104] On the other hand, the body surface patch of Reference Example 1 had a thin base material and insufficient bending stiffness (bending resistance), so it had no firmness and was difficult to handle when applied. Also, the body surface patch of Reference Example 2 had a thick base material and a too large load when stretched, so it was uncomfortable to apply and had poor followability to the movement of the body surface.
[0105] Thus, the body surface patch according to the present technology has a base material thickness of 20 to 90 μm and an adhesive layer thickness of 40 to 160 μm, and the adhesive layer contains at least a radiation-curable resin and a hydrophilic polymer compound, so that even with a simple configuration that does not include a carrier sheet, it is easy to handle when applied and has flexibility and stretchability that allows it to conform well to the body surface after application, and also reduces flow of the adhesive. [Explanation of symbols]
[0106] 1. Body surface patch 2 Base material 3 Adhesive layer 4 Adhesive protection layer
Claims
1. a substrate having a top surface and a bottom surface; a pressure-sensitive adhesive layer covering at least a portion of the bottom surface of the substrate; A peelable adhesive protective layer that covers the surface of the adhesive layer, The thickness of the substrate is 20 to 90 μm, and the thickness of the pressure-sensitive adhesive layer is 40 to 160 μm, The total thickness of the substrate and the pressure-sensitive adhesive layer is 60 to 250 μm, The pressure-sensitive adhesive layer contains at least a radiation curable resin and a hydrophilic polymer compound, The load at extension at 20% displacement is 3.3 N / 20 mm or more and 6.1 N / 20 mm or less, and the peak of the probe tack measured under the following probe tack test conditions is 10 gf or more and 67.3 gf or less, and the integrated value of the probe tack is 20 to 42.3 gfs. A patch for application to a body surface (excluding a patch for application to a body surface in which the adhesive layer contains a reactive diluent that reacts with the radiation curable resin). <Probe tack test conditions> Measuring equipment: TACKINES TESTER (manufactured by RHESCA) Temperature: 37℃ Probe diameter: 5 mm Probe descending speed: 30 mm / min Probe pressing load: 10g for 2 seconds Probe lifting (pulling away) speed: 30 mm / min
2. The pressure-sensitive adhesive layer is The radiation curable resin is 40 to 90% by mass of an ultraviolet curable resin, The body surface patch according to claim 1, comprising 5 to 35% by mass of the hydrophilic polymer compound.
3. 3. The body surface patch according to claim 1, wherein the pressure-sensitive adhesive layer comprises 5 to 25% by mass of a non-functional acrylic polymer.
4. The pressure-sensitive adhesive layer is The radiation curable resin is 50 to 80% by mass of an ultraviolet curable (meth)acrylate resin, As the hydrophilic polymer compound, 10 to 30 mass % of one or more hydrophilic polymer compounds selected from sodium carboxymethylcellulose, pectin, and gelatin; 4. The body surface patch according to claim 3, comprising 10 to 20% by mass of a non-functional acrylic polymer that is liquid at room temperature (20 to 30° C.).
5. 5. The patch for body surface according to claim 1, which has a flow rate of 10% or less after water absorption.
6. The patch for body surface according to any one of claims 1 to 5, which has a visible light transmittance at a wavelength of 550 nm of 5.0% or more.
Citation Information
Patent Citations
Picture transmitter
JP1981078288A
Medical sticking material
JP1997154872A
Felbinac-containing plaster
JP2001039864A
Patch for skin during anticancer drug treatment
JP2010018564A
Moldable hydrocolloid material
JP2014176646A